A Review to Understand the Advancements and Challenges in Wireless Technology - Nishtha Saroha, (AG Volumes, 2022)
Wireless technology has developed greatly over the years. New and developing technologies like drones, robots, self-driven cars, and new medical gadgets are coming into existence is the necessity of the "Internet of Things" (IOT) will be the cornerstone for the development of such technologies. This paper review will look at several Wireless technology developments which found their position in the top 10 and revolutionized the way individuals and organizations interact in the future. These trends may come from enterprises’ desire to be more adaptable to market and data security concerns, consumer needs, Internet of things, and so on.